Pers, pembangunan, dan kekuasaan: Studi historis organisasi Persatuan Wartawan Indonesia di Kalimantan Timur tahun 1981-1998 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
During the New Order era, the press in Indonesia operated under strict state control, resulting in the existence of only one official journalists’ organization, the Indonesian Journalists Association (PWI). This study aims to: (1) examine the background and process of the establishment of PWI in East Kalimantan, (2) analyze the role of PWI as a professional organization in East Kalimantan, and (3) assess the impact of PWI in the region. This research employs the historical method, which consists of four stages: heuristics, source criticism, interpretation, and historiography. The findings reveal that the establishment of the East Kalimantan Branch of PWI during the New Order was driven by the need to standardize the journalism profession. The formation process occurred in several stages: initially as a Representative Preparation, then as a PWI Representative, and finally as the East Kalimantan Branch of PWI. As a professional organization, PWI played a crucial role in protecting journalists’ work-related risks, enhancing journalistic professionalism, and improving members’ welfare. The impact of PWI in East Kalimantan was significant for both journalists and society, including increased professional competence, better welfare for journalists, more accurate information dissemination, and heightened public awareness.
Keywords: East Kalimantan; Journalism profession; professional organization; PWI, New Order